The validity of Physical Learning Device Based on Discovery Learning Model Assisted by Virtual Laboratory - Apriani, Ni Wayan Riska; Doyan, Aris; Sridana, Nyoman; Susilawati, Susilawati (Postgraduate, University of Mataram, 2020)
The purpose of this study was to determine the validity of physics learning devices based on discovery learning models assisted by virtual laboratories. This type of research is research and development that refers to the 4-D development model. The 4-D development model consists of four steps namely, defining, designing, developing and disseminating. Learning tools developed in the form of syllabi, lesson plans, student worksheets, and evaluation instruments. This article only focuses on the process of testing the validity of learning tools by experts. The results of the analysis of the validity and reliability state the learning device is categorized as valid and can be used in physics learning.